Implementation of a Cooperative Learning Model in 21st Century Indonesian Language Learning in Madiun City Vocational Secondary Schools in 2022/2023 - V. Teguh Suharto; Wahyuningsih; Dedy Richi Rizaldy; Pramudita Septiani (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Today's learning process is constructivist in nature through students experiencing what is learned cooperatively and constructing experience into knowledge. This learning model includes an active, natural, process-based learning model that is driven by high learning motivation to master competencies for completing tasks/problems. After having high motivation, with self-cooperative learning students will continue to experience learning and construct experience into knowledge. Knowledge will continue to be refined through the process of experience through accommodation and assimilation events in real life.